Minimally invasive surgical treatment of Robert's uterus with missed miscarriage: case report - Houyu Yang; Yuanjunzi Shi; Gang Ji (Taylor & Francis Group, 2024)
Robert's uterus was firstly reported in 1970, it's a rare Müllerian duct anomaly with 2 intra-uterine cavities divided by asymmetrical septum. One of the cavities is completely obstructed to cervix by septum and menstruation fluid retents in this blind cavity, periodical pelvic pain during menstruation can lead attendance to hospital. We report a gravida of Robert's uterus with missed abortion in the blind cavity, who had mild dysmenorrhoea since adolescent age, diagnosed and treated by minimally invasive surgical methods. To our knowledge, it's a previously unreported case which gynaecologists terminated pregnancy in blind cavity of Robert's uterus without resecting the septum while dysmenorrhoea relieved entirely and postoperative volume of menstruation stayed the same as preoperative.